Comparative results between three protocols for achieving highly exfoliated epoxy-clay nanocomposites - Hutchinson, J. M.; Shiravand, F.; Calventus, Y.; Ferrando, F. (Polimery, 2014)
Three different methods of fabricating polymer layered silicate (PLS) nanocomposites based upon a tri-functional epoxy resin are compared in respect of the nanostructure and impact energy of the cured nanocomposites. The three methods are designed to maximise the amount of intra-gallery reaction that takes place during cure, and this paper examines separately the effects of: (i) increasing the isothermal cure temperature; (ii) preconditioning the resin/clay mixture; and (iii) incorporating an initiator of homopolymerisation within the clay galleries. It is shown that each of these methods increases the degree of exfoliation in the cured nanocomposite, and that this improved nanostructure correlates also with an increase in the impact energy.